Effect of Blood Bags Storage Time on The Quality of HIV Pre Transfusion Test Result: Preliminary Study in Blood Bank’s dr. Ben Mboi Ruteng Manggarai District, East Nusa Tenggara Province - Yani Suryani; Opik Taupiqurrohman; Yohanes Reynerius (Program Study of Biology, Science and Technology Faculty, UIN Maulana Malik Ibrahim Malang, 2022)
Research on the effect of storage time on blood quality has been conducted. The purpose of this study is to determine the quality changes caused by the length of storage. The test parameter is the change in blood to become HIV positive. The blood testing process is carried out by immune chromatography on blood that has been stored for 2 weeks, 3 weeks, 4 weeks and 5 weeks. Test results show changes in blood quality during storage. Time does not show a difference in changes in blood quality, however it needs to be aware, because the stored blood changes.